Enhancing workplace safety and ergonomics with motion capture systems: Present state and a case study - Vujica-Herzog, Nataša (Advances in production engineering and management, 2024)
A motion capture system (MoCap) records and tracks the real-time movements of objects or people, generating data that can also be used for ergonomic analysis. Using specialised cameras and sensors, these systems translate movements into digital data that can animate figures or objects in a digital environment. While they are widely used in industries such as film, video games, sports, virtual reality and biomechanics, MoCap systems can also be used in the ergonomic design of workplaces. These systems allow researchers to analyse human movements, identify risks such as repetitive movements, awkward postures or excessive forces and develop solutions to improve safety, comfort and performance. The collected data helps to optimise workplace design, products and processes, reduce musculoskeletal disorders and improve well-being. Recent advancements have made motion capture systems highly sophisticated and capable of recognising subtle movements and expressions with exceptional precision. This paper consists of two parts: a concise literature review and a case study. The literature review explores the application of advanced human motion capture technologies in manufacturing and highlights their potential for ergonomic improvements. The case study illustrates these applications and provides practical insights into how motion capture can transform the design and functionality of workplaces.
Keywords: analiza delovnih mest; biomechanical research; biomehanske raziskave; ergonomic risks; ergonomics; ergonomija; ergonomska tveganja; industrija 4.0; industry 4.0; motion capture; oblačila Xsens; virtual reality; virtualna resničnost; workplace analysis; xsens suit; zajem gibanja